2015
DOI: 10.1002/masy.201400071
|View full text |Cite
|
Sign up to set email alerts
|

The Potential of Perlite as an Odour‐Adsorbing Fillers in Natural Rubber Vulcanizates

Abstract: The objective of this research was to reduce an offensive odour by using perlite as an odour-adsorbing filler. Perlite was mixed with highly odorous STR20 and RSS5. Perlite content was varied at 0, 10, 20 and 30 phr. The ability to reduce odour by sensory method and GC-MS were examined. Cure characteristics and mechanical properties, such as tensile strength, hardness and abrasion resistance, were also determined. From the sensory method, the odour reduction efficiency increased with increasing perlite content… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Zhang X. et al exhibited that thermal conductivity of polyethylene glycol was improved with the addition of PER [31]. Rattanaplome et al showed that PER had a potential of odor adsorbing additive for natural rubber products [32].…”
Section: Introductionmentioning
confidence: 99%
“…Zhang X. et al exhibited that thermal conductivity of polyethylene glycol was improved with the addition of PER [31]. Rattanaplome et al showed that PER had a potential of odor adsorbing additive for natural rubber products [32].…”
Section: Introductionmentioning
confidence: 99%